2014
DOI: 10.1080/15374416.2014.930689
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Anxiety and Depression in Relation to the Social Functioning of Young Adolescents With ADHD

Abstract: Objective-The present study examined anxiety and depressive symptoms in relation to the social functioning of young adolescents with attention-deficit/hyperactivity disorder (ADHD) and builds upon prior work by incorporating youths' self-reports of internalizing symptoms and examining distinct anxiety and depression dimensions in order to increase specificity.Method-Participants were 310 young adolescents (ages 10-14; 71% male;78% Caucasian) diagnosed with ADHD. Youth provided ratings of anxiety/depression, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 75 publications
(104 reference statements)
1
25
2
1
Order By: Relevance
“…The findings regarding CD severity and depression as risk factors are partially consistent with prior findings indicating that comorbid diagnoses with ADHD have either no effect on or exacerbate the social impairment of youth with ADHD (Becker et al, 2012; Becker et al, 2015). Dissimilar from Becker et al, we found that ODD severity was not associated with social impairment.…”
Section: Discussionsupporting
confidence: 87%
“…The findings regarding CD severity and depression as risk factors are partially consistent with prior findings indicating that comorbid diagnoses with ADHD have either no effect on or exacerbate the social impairment of youth with ADHD (Becker et al, 2012; Becker et al, 2015). Dissimilar from Becker et al, we found that ODD severity was not associated with social impairment.…”
Section: Discussionsupporting
confidence: 87%
“…For example, some results indicate that symptoms of depression, but not anxiety, exacerbate the association between symptoms of ADHD and social problems (Becker, Langberg, Evans, Girio-Herrera, & Vaughn, 2014). In addition, among youth with ADHD, MDD is associated with more severe impairments and poorer developmental outcomes than those associated with either disorder alone (Daviss, 2008).…”
Section: Depression As a Moderatormentioning
confidence: 99%
“…Regarding different levels of depression corresponding to different levels of social problems, findings indicate that among the internalizing disorders that co-occur with ADHD, MDD is more often associated with problems in functioning than others. For example, some results indicate that symptoms of depression, but not anxiety, exacerbate the association between symptoms of ADHD and social problems (Becker, Langberg, Evans, Girio-Herrera, & Vaughn, 2014). In addition, among youth with ADHD, MDD is associated with more severe impairments and poorer developmental outcomes than those associated with either disorder alone (Daviss, 2008).…”
Section: Depression As a Moderatormentioning
confidence: 99%
“…It is important to recognise children with ADHD who present with symptoms of depression, as its presence alongside ADHD is associated with poorer academic and social functioning (Becker, Langberg, Evans, Girio‐Herrera, & Vaughn, ; Blackman, Ostrander, & Herman, ). Additionally, depression itself is more severe when comorbid with ADHD, with evidence suggesting an earlier onset, a longer duration, greater depression‐associated impairment, a higher suicidality rate and a greater likelihood of psychiatric hospitalisation (Biederman et al., ).…”
Section: Introductionmentioning
confidence: 99%